Revealing the Benefits of Zam-Zam Water in the Perspective of Islam and Health - Wahyudi, Hakmi; Amiruddin, Muhammad; Arriziq, Abbas; Maula, Romlatul; Kusuma, Muhammad A'laa Muniron; Nabila, Inayah Nailun (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 1 (2022): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2022)
Health is one of the most essential things that everyone should have. One thing that needs to be considered in maintaining health is food and drink. Islam is a complex religion because eating and drinking have been regulated in Islam, as stated in the Al-Quran and Hadith. One of them is about zam-zam water. Some of the author's goals are to find out the existence of zam-zam water in the Qur'an and hadith, know the content of zam-zam water, and the method of treatment with zam-zam water. The result is that zam-zam water has a special existence, as do many Qur'ans and hadiths discussing zam-zam water. Zam-zam water has various health benefits for healing diseases such as cancer, food poisoning, burns, etc. Regarding how to use it, there is no specific or unique way of using zam-zam water for treatment. Zam-zam water will be helpful depending on its intention or purpose.